AhR ligand aminoflavone suppresses α6‐integrin–Src–Akt signaling to attenuate tamoxifen resistance in breast cancer cells. Issue 1 (4th August 2018) - Campbell, Petreena S.; Mavingire, Nicole; Khan, Salma; Rowland, Leah K.; Wooten, Jonathan V.; Opoku‐Agyeman, Anna; Guevara, Ashley; Soto, Ubaldo; Cavalli, Fiorella; Loaiza‐Pérez, Andrea Irene; Nagaraj, Gayathri; Denham, Laura J.; et al.
Abstract : More than 40% of patients with luminal breast cancer treated with endocrine therapy agent tamoxifen demonstrate resistance. Emerging evidence suggests tumor initiating cells (TICs) and aberrant activation of Src and Akt signaling drive tamoxifen resistance and relapse. We previously demonstrated that aryl hydrocarbon receptor ligand aminoflavone (AF) inhibits the expression of TIC gene α6‐integrin and disrupts mammospheres derived from tamoxifen‐sensitive breast cancer cells. In the current study, we hypothesize that tamoxifen‐resistant (TamR) cells exhibit higher levels of α6‐integrin than tamoxifen‐sensitive cells and that AF inhibits the growth of TamR cells by suppressing α6‐integrin–Src–Akt signaling. In support of our hypothesis, TamR cells and associated mammospheres were found to exhibit elevated α6‐integrin expression compared with their tamoxifen‐sensitive counterparts. Furthermore, tumor sections from patients who relapsed on tamoxifen showed enhanced α6‐integrin expression. Gene expression profiling from the TCGA database further revealed that basal‐like breast cancer samples, known to be largely unresponsive to tamoxifen, demonstrated higher α6‐integrin levels than luminal breast cancer samples. Importantly, AF reduced TamR cell viability and disrupted TamR mammospheres while concomitantly reducing α6‐integrin messenger RNA and protein levels. In addition, AF and small interfering RNA against α6‐integrin blocked tamoxifen‐stimulated proliferation of TamR MCF‐7 cells and further sensitized these cells to tamoxifen. Moreover, AF reduced Src and Akt signaling activation in TamR MCF‐7 cells. Our findings suggest elevated α6‐integrin expression is associated with tamoxifen resistance and AF suppresses α6‐integrin–Src–Akt signaling activation to confer activity against TamR breast cancer. Abstract : Tamoxifen‐resistant (TamR) human breast cancer cells and tumors from patients who have relapsed on tamoxifen exhibit elevated α6‐integrin levels. Aryl hydrocarbon receptor ligand aminoflavone blocks tamoxifen‐stimulated TamR cell proliferation and suppresses α6‐integrin–Akt–Src signaling activation.